LAW ENFORCEMENT AGAINST PERPETRATORS OF FOREST AND LAND BURNS IN JURISDICTION TANJUNG JABUNG TIMUR RESORT POLICE - Firman Adiansyah; Sunardi; Moh. Muhibbin (International Journal of Cultural and Social Science, 2025)
Forest and land fires (karhutla) in East Tanjung Jabung Regency, Jambi Province, remain a serious problem despite being regulated by Law Number 32 of 2009 concerning Environmental Protection and Management and the Forestry Law. This research aims to analyze the implementation of law enforcement against perpetrators of forest and land fires and to identify the obstacles faced by the East Tanjung Jabung Police. The method used is empirical legal with a sociological, legislative, and conceptual approach, thru interviews, observation, and literature study. The data was analyzed descriptively and qualitatively to describe the suitability between legal norms and their implementation in the field. The research results show that law enforcement has proceeded according to procedure, but still focuses on individual perpetrators, while corporations are rarely penalized. The main obstacles include limited evidence, weak inter-agency coordination, a shortage of environmental investigators, and low public legal awareness. The application of the principle of strict liability is also not yet optimal. This research concludes that the effectiveness of forest and land fire law enforcement requires strengthening cross-sectoral coordination, increasing the capacity of law enforcement officers, and providing legal education to the public in order to achieve firm and just law enforcement.